STEM-based disaster mitigation digital learning model: A means of improving primary school students’ psychological preparedness for disaster - Arwin, Arwin; Kenedi, Ary Kiswanto; Anita, Yesi; Mardin, Asna; Yulistina, Nova (International Journal of Innovative Research and Scientific Studies, 2025)
Conventional learning models were considered less effective at developing children’s psychological preparedness. Previous studies have produced a STEM-based Disaster Mitigation Digital Learning Model that has been certified legitimate by experts; nevertheless, more research is required to determine its effect on disaster psychological preparedness in children. This study sought to determine the effectiveness of this STEM-based learning model in enhancing children’s psychological preparedness for disasters. The method utilized was a quasi-experiment with a non-equivalent control group design. The study included 600 grade 5 elementary school students. The research tool was a validated psychological disaster preparedness questionnaire, and the data were analyzed for the normality test, homogeneity test, paired sample t-test, and independent sample t-test. The results revealed a substantial difference between the mean post-test of the experimental and control groups. Children in the experimental group who learned using the STEM-based learning model demonstrated more psychological disaster preparedness than the control group. This finding demonstrated that a STEM-based digital learning model was more effective than traditional techniques in shaping disaster psychological preparedness. This model was intended to provide children with improved adaption abilities and psychological preparedness, allowing them to be more resilient and ready to confront potential crises in the future.